ANALYSIS OF BOERJA GOAT ANIMAL BUSINESS PROFITABILITY (Case Study at CV. Agriranch Kelurahan Tawangargo, Kecamatan Karangploso, Kabupatan Malang) - Sin, Maria Yohaneta; Sumarno, Sumarno; Santoso, Erik Priyo; Murti, Ariani Trisna (Fakultas Pertanian, 2019)
The purpose of the research is to know the amount of income and the value of profitability of the goat livestock business. The research was conducted at "CV. Agriranch" Tawangargo Village, Karangploso Subdistrict, Malang Regency on July 05 to August 05 2018 with a population in 2015,2016,2017 with 126 individuals, 150 tails, 222 tails. The method used is Case Study method with data analysis on Income, Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Investment (ROI) and Payback Period (PP). .Revenues in 2015-2017 amounted to Rp.24,334,000, Rp. 33,856,000, Rp. 42,630,000. The GPM value from 2015-2017 was 19.71%, 20.64%, 21.43%. The 2015 NPM value was 18.73%, 2016 was 19.61%, and 2017 was 20, 86%. The value of ROI in 2015-2017 with 11.55%, 16.08%, 20.74% respectively. PP value in 2015-2017 was 1.62 years, 1.21 years and 1 years.The results of profitability analysis show that boerja goat business in CV. Agriranch is feasible to be developed in terms of the value of GPM, NPM, and ROI which increases every year, while the value of Payback Period decreases from year to year so the company benefits. Tujuan penelitian untuk mengetahui besarnya pendapatan dan nilai profitabilitas usaha ternak kambing boerja. Penelitian dilaksanakan di “CV.Agriranch“Kelurahan Tawangargo, Kecamatan Karangploso, Kabupaten Malang pada bulan 05 juli sampai 05 agustus 2018 dengan populasi pada tahun 2015,2016,2017 dengan masing-masing 126 ekor, 150 ekor, 222 ekor. Metode yang digunakan study kasus atau Case Study method dengan analisis data mengenai Pendapatan, Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Investment (ROI) dan Payback Period (PP). Pendapatan pada tahun 2015-2017 sebesar Rp.24.334.000, Rp. 33.856.000, Rp. 42.630.000. Nilai GPM dari tahun 2015-2017 sebesar 19,71%, 20,64 %, 21,43 % .,Nilai NPM pada tahun 2015 sebesar 18,73%, tahun 2016 sebesar 19,61%, dan tahun 2017 sebesar 20,86%., Nilai ROI pada tahun 2015 -2017 dengan masing-masing 11,55%, 16,08%, 20,74%. Nilai PP pada tahun 2015-2017 sebesar 1,62 tahun, 1,21 tahun dan 1 tahun. Hasil analisis profitabilitas menunjukkan bahwa Usaha ternak kambing boerja di CV. Agriranch layak untuk dikembangkan ditinjau dari nilai GPM, NPM, dan ROI mengalami peningkatan setiap tahunnya, sedangkan nilai Payback Period menurun dari tahun ke tahun sehingga perusahaan mendapatkan keuntungan